Bio-Monitoring of Aquatic Environment: Hematological and Biochemical Changes in Grass Carp due to Toxicity of Emamectin Benzoate, Acetochlor, and Topsin-m - Badshah, Khan Dil; Riaz, Bilal; Ejiz, Rameen; Khan, Ashfaq A.; Mehdi, Kamran; Khan, Saqib; Riaz, Sania; Ahmad, Kamil; Ahmed, Naseer (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research The grass carp was the species used in this study due to its ecological significance and sensitivity to pollutants. The study examined both acute and chronic toxicity effects of pesticides on grass carp to understand their immediate and long-term impact. Harmful effects on hematological profile of Grass carp fish were observed and hence are deleterious to aquatic life and environment. Biochemical changes observed, Emamectin Benzoate found more toxic than Acetochlor and Acetochlor is more toxic than Topsin-M. Abstract This study investigates the novel combined effects of Emamectin Benzoate (pesticide), Acetochlor (herbicide), and Topsin-M (fungicide) on hematological and biochemical profiles in grass carp (Ctenopharyngodon idella), to fill critical gaps in understanding their ecotoxicological impacts on aquatic health and sustainable fisheries. Fishes from farm in Gujranwala were acclimatized in a freshwater aquarium laboratory for a week, then divided into four groups (E1, E2, E3, and E4) exposed to pesticide, herbicide, and fungicide concentrations for 5 and 14 days. Blood samples were collected for hematological and biochemical parameters. Exposure to Emamectin Benzoate induces significant increase in WBCs, neutrophils, MCV, MCH, and platelets, while a significant decrease was found in RBCs, lymphocytes, hemoglobin, PCV, and MCHC concentration. Acute toxicity of Acetochlor showed an increase in WBCs, neutrophils, MCV, MCH contents, and platelets, while a decrease in RBCs, lymphocytes, hemoglobin, PCV, and MCHC contents was noted. Effects of Topsin-M showed an increase in WBCs, neutrophils, MCV, MCH contents, and platelets. However, a significant decrease in RBCs, lymphocytes, hemoglobin, PCV, and MCHC contents has been observed. It reveals that Uric acid, serum lipase, Sodium, Phosphorous, Bilirubin, and Potassium increased significantly. Exposure to chemicals induced significant declines in the levels of Lactate dehydrogenase (LDH), Triglyceride, HDL Cholesterol, SGPT (ALT) Creatinine, and ALK Phosphatase which caused illness in fish. This study shows potential for biomonitoring of aquatic environments.